Social and Human Capital Development in Village-Owned Entreprises: Implications for Performance Enhacement - Rahmawati, Emma; Ella, Susy; Novi Andari, Rosita; Hilmiati, Nurul (Departement of Communication and Community Development Sciences, Faculty of Human Ecology, 2024)
The count of Village-Owned Enterprises (VOEs) across Indonesia has consistently escalated annually. However, the optimal utilization of VOEs in labor absorption remains unrealized because of suboptimal business performance. Thus, the formulation of a performance-enhancement model for VOEs is imperative. The primary objective of this study was to identify the challenges, propose solutions, and formulate a comprehensive model to improve the performance of VOEs. Data were collected using a mixed methods approach. Data collection used a mixed methods approach through diverse channels including observation, questionnaires, Focus Group Discussions (FGDs), and documentation. The resultant data were subjected to analytical techniques, including descriptive analysis, fishbone diagrams, and Structural Equation Modelling (SEM) for rigorous evaluation. The findings highlight that human resources are the core obstacle contributing to VOE underperformance. Employees regard interpersonal skills as the foremost dimension in cultivating social capital, significantly shaping human capital development. In terms of performance, the variable with the highest agreement was innovation capability. As such, selecting Social Capital and Human Capital as the foundational pillars for the performance improvement model of VOEs in the West Bandung Regency was both fitting and well-founded.